Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

1. Solve the system of linear equations:

[tex]\[
3n + 2y = 1
\][/tex]

[tex]\[
4m - 5y = -14
\][/tex]

using:
a) inverses
b) determinants


Sagot :

Sure, let's solve the given system of linear equations using the given methods:

The system of equations is:
[tex]\[ 3m + 2y = 1 \][/tex]
[tex]\[ 4m - 5y = -14 \][/tex]

### a) Using Inverses

Step 1: Write the system in matrix form:

[tex]\[ A \mathbf{x} = \mathbf{b} \][/tex]

where
[tex]\[ A = \begin{pmatrix} 3 & 2 \\ 4 & -5 \\ \end{pmatrix} \][/tex],
[tex]\[ \mathbf{x} = \begin{pmatrix} m \\ y \\ \end{pmatrix} \][/tex],
and
[tex]\[ \mathbf{b} = \begin{pmatrix} 1 \\ -14 \\ \end{pmatrix}. \][/tex]

Step 2: Find the inverse [tex]\( A^{-1} \)[/tex] of matrix [tex]\( A \)[/tex]:

[tex]\[ A^{-1} = \begin{pmatrix} 0.2173913 & 0.08695652 \\ 0.17391304 & -0.13043478 \\ \end{pmatrix} \][/tex]

Step 3: Multiply the inverse of the matrix [tex]\( A \)[/tex] by the vector [tex]\( \mathbf{b} \)[/tex] to get [tex]\( \mathbf{x} \)[/tex]:

[tex]\[ \mathbf{x} = A^{-1} \mathbf{b} = \begin{pmatrix} -1 \\ 2 \\ \end{pmatrix} \][/tex]

So, the solution using the inverse method is:
[tex]\[ m = -1, \quad y = 2 \][/tex]

### b) Using Determinants (Cramer's Rule)

Step 1: Calculate the determinant of matrix [tex]\( A \)[/tex]:

[tex]\[ \text{det}(A) = \begin{vmatrix} 3 & 2 \\ 4 & -5 \\ \end{vmatrix} = (3 \cdot (-5)) - (2 \cdot 4) = -15 - 8 = -23 \][/tex]

Step 2: Compute the determinant of matrix obtained by replacing the first column of [tex]\( A \)[/tex] with [tex]\( \mathbf{b} \)[/tex] to find [tex]\( \text{det}(A_m) \)[/tex]:

[tex]\[ A_m = \begin{pmatrix} 1 & 2 \\ -14 & -5 \\ \end{pmatrix} \][/tex]

[tex]\[ \text{det}(A_m) = \begin{vmatrix} 1 & 2 \\ -14 & -5 \\ \end{vmatrix} = (1 \cdot (-5)) - (2 \cdot (-14)) = -5 + 28 = 23 \][/tex]

Step 3: Compute the determinant of matrix obtained by replacing the second column of [tex]\( A \)[/tex] with [tex]\( \mathbf{b} \)[/tex] to find [tex]\( \text{det}(A_y) \)[/tex]:

[tex]\[ A_y = \begin{pmatrix} 3 & 1 \\ 4 & -14 \\ \end{pmatrix} \][/tex]

[tex]\[ \text{det}(A_y) = \begin{vmatrix} 3 & 1 \\ 4 & -14 \\ \end{vmatrix} = (3 \cdot (-14)) - (1 \cdot 4) = -42 - 4 = -46 \][/tex]

Step 4: Use Cramer's Rule to find [tex]\( m \)[/tex] and [tex]\( y \)[/tex]:

[tex]\[ m = \frac{\text{det}(A_m)}{\text{det}(A)} = \frac{23}{-23} = -1 \][/tex]

[tex]\[ y = \frac{\text{det}(A_y)}{\text{det}(A)} = \frac{-46}{-23} = 2 \][/tex]

So, the solution using determinants (Cramer's Rule) is:
[tex]\[ m = -1, \quad y = 2 \][/tex]

In both methods, we obtained the same solution:
[tex]\[ m = -1, \quad y = 2 \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.